2018
DOI: 10.1094/phyto-02-17-0065-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climatic Variables on Abundance and Dispersal ofLecanosticta acicolaSpores and Their Impact on Defoliation on Eastern White Pine

Abstract: The disease complex white pine needle damage (WPND), first reported in 2006, has now escalated to an epidemic state across the northeastern United States. Although this complex is composed of several fungal species, Lecanosticta acicola is considered to be the primary causal agent. Knowledge regarding the epidemiology, specific climatic factors that affect the spread of L. acicola on eastern white pine (Pinus strobus) in natural forest settings, and potential risks repeated defoliation may have on tree health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…In Wisconsin, two peaks of conidial release were recorded, with the first peak in early summer when young pine needles are present and the second in late summer (Skilling and Nicholls, ), which was similar to that found in the northeastern USA (Wyka et al . ). In Japan, it was found that conidia were produced by the pathogen from early spring to autumn with peak dispersal in mid‐summer.…”
Section: Biology and Disseminationmentioning
confidence: 97%
See 3 more Smart Citations
“…In Wisconsin, two peaks of conidial release were recorded, with the first peak in early summer when young pine needles are present and the second in late summer (Skilling and Nicholls, ), which was similar to that found in the northeastern USA (Wyka et al . ). In Japan, it was found that conidia were produced by the pathogen from early spring to autumn with peak dispersal in mid‐summer.…”
Section: Biology and Disseminationmentioning
confidence: 97%
“…Conidia and ascospores are released throughout the year at temperatures ranging from -5.5 to 28 °C (Kais, 1971;Siggers, 1944;Wyka et al, 2018). However, warm and wet weather is particularly conducive for the development of BSNB, irrespec tive of whether infection takes place by sexual or asexual spores.…”
Section: B I O Log Y a N D D I Ss E M I N At I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent establishment of this pathogen in southern Sweden may also pose a serious risk for Scots pine ( Pinus sylvestris ) which has large economic importance for the forest sector in Sweden. Dispersal of L. acicola is strongly influenced by climate where the frequency (rather than amount) of rainfall seems to be of primary importance (Wyka et al, ), and where relative humidity and temperature affect spore abundance. Such conditions are conducive for the establishment of this pathogen not only in Estonia, but also in southern Sweden.…”
Section: Resultsmentioning
confidence: 99%